Polar Bear Fossil and Archaeological Records from the Pleistocene and Holocene in Relation to Sea Ice Extent and Open Water Polynyas. (6th May 2022) - Crockford, Susan J.
The polar bear ( Ursus maritimus ) is the apex predator of the Arctic but its distribution throughout the Pleistocene and Holocene has not previously been reported. Although natural death specimens of this species ('fossils') are rare, archaeological remains are much more common. This historical compilation presents the record of known ancient polar bear remains from fossil and archaeological contexts before AD 1910. Most remains date within the Holocene and derive from human habitation sites within the modern range of the species, with extralimital specimens documented in the north Atlantic during the late Pleistocene and in the southern Bering Sea during the middle Holocene reflecting natural expansions of sea ice during known cold periods. The single largest polar bear assemblage was recovered from an archaeological site on Zhokhov Island, Russia, occupied ca. 8, 250–7, 800 a BP during the warmer-than-today Holocene Climatic Optimum: 5, 915 polar bear bones were recovered, representing 28% of all remains identified. Polar bear fossils and archaeological remains across the Arctic are most often found in proximity to areas where polynyas (recurring areas of thin ice or open water) are known today and which likely occurred in the past, including for the oldest known fossil from Svalbard (ca. 130–115 k a BP) and the oldest known archaeological specimens from Zhokhov Island (ca. 8, 000 a BP). This pattern indicates that as they do today, polar bears may have been most commonly found near polynyas throughout their known historical past because of their need for ice-edge habitats at which to hunt seals.